Bio-inspired magnetic molecularly imprinted polymers based on Pickering emulsions for selective protein recognition. (9th September 2016) - Sun, Yanhua; Chen, Jian; Li, Yuqing; Li, Hui; Zhu, Xiaohong; Hu, Yuwei; Huang, Shen; Li, Jianbing; Zhong, Shian
Abstract : Hydrophobic halloysite nanotube stabilized Pickering emulsions and their application in protein separation. Abstract : Novel magnetic molecularly imprinted polymers (MMIPs) based on halloysite nanotube stabilized Pickering emulsion polymerization were successfully prepared using a facile approach for the high recognition and separation of proteins in aqueous solutions. The MMIPs were synthesized based on the self-polymerization of dopamine in weak alkaline solution in the presence of template protein. During the self-polymerization of dopamine in the water phase, the template proteins were embedded in polydopamine (PDA), and after the removal of the embedded template proteins, magnetic bovine hemoglobin (BHb) imprinted PDA@MHNTs (MHNTs, magnetic halloysite nanotubes) with complementary cavities were eventually obtained. The resulting samples were analyzed by Fourier transmission infrared (FT-IR) spectrometry, scanning electron microscopy (SEM), vibrating sample magnetometry (VSM) and thermogravimetric analysis (TGA). The prepared MMIPs showed high adsorption capacity, good selectivity, rapid kinetic binding (70 min), stability (only 9% decrease after four cycles) and magnetic separability (3 min), which would endow the MMIPs with great potential in the field of protein separation and purification, biosensing, proteomics and biotherapy.